KORELASI ANTARA MOTIVASI BELAJAR DENGAN PRESTASI BELAJAR PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM (PAI) BERBASIS ONLINE SISWA KELAS VIII SMP NEGERI 2 WATAMPONE - Syahriana Syahriana; Muh Yahya (Atta'dib Jurnal Pendidikan Agama Islam, 2022)
This study aims to determine the correlation between learning motivation and student achievement during online-based Islamic Religious Education learning. The type of research used in this research is quantitative research with the research location in SMP Negeri 2 Watampone. The population in this study were all class VIII SMP Negeri 2 Watampone. The sample size uses the Harry King Nomogram and the sampling technique uses random sampling. The sample in the study was 112 but after testing the outlier data taken 90. Data collection used a questionnaire instrument and only documentation. Data were analyzed descriptively and inferentially with SPPS v.26 assistance program. The results showed that there was a correlation between learning motivation and learning achievement during online-based Islamic Religious Education learning.Keywords: learning motivation, learning achievement